How to combine performance analysis, swimming technique testing and training planning - Arellano, R. (First international symposium sciences and practices in swimming, 2006)
Planning training technique and its control is one of the least developed aspects in modern coaching methodology, which focuses more on the development of general training periods or bio-medical control of performances. The current Situation allows the application of many means of objective assessment of technique that are often, with the coaches' possibilities, or are available in Training Centres (CARs in Spain) or some Research Centres such us developed in our Faculty. Proposals such as those described in the present work are a step forward in the development of a methodology in the evaluation of swimming technique related to the swimmer's training cycles.